How do people select their residential locations in Egypt? The case of Alexandria. (February 2017) - Ibrahim, Mohamed R.
Abstract: Affordable housing unit is still a rare resource in Egypt, despite the active role of the government to reform housing policies. The deficits of affordability and housing supply have been addressed intensively in the framework of the Egyptian housing policies. Indeed, housing prices and market conditions can be among the factors that influence the choices of the people to select certain residential locations. However, there are still no significant impacts that show affordability as the primary factor in the self-selection process of residential locations in Egypt. This complicates housing development scenario in Egypt. This paper highlights various debates concerning some of the current assumptions regarding housing development in Egypt. Focusing on Alexandria, Egypt, the main factors influencing current residential location choices are shown to be the availability of public transportation, followed by living in a good neighborhood and housing affordability. Highlights: Interdisciplinary study for housing market, travel behavior and housing self-selection in Egypt Theoretical approach for housing location choice in Egypt Housing Survey in the city of Alexandria The role of housing affordability, built environment, public transportation, and travel behavior in selecting residential locations in Alexandria, Egypt.